CORAL REEF DISTRIBUTION MAPPING CASE STUDY OF SETAN ISLAND WATERS, WEST SUMATRA - Pambudi, Bagas Ariya; Thamrin, Thamrin; Elizal, Elizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The research was conducted in May 2023 in Setan Island, West Sumatra. The study aimed to map the distribution of coral reefs, test the accuracy of the resulting map, and determine the condition of coral reef cover on Setan Island. The methods used are remote sensing methods using Sentinel-2 satellite imagery and field survey methods to validate the distribution of coral reefs resulting from image data processing (Groundcheck) and to observe the condition of coral reefs using the Underwater Photo Transect (UPT) method. Determination of sampling locations to ground check the distribution of coral reefs using a Stratified random sampling method while determining sampling locations for observations of coral reef cover using a purposive sampling method. The study results obtained a coral reef distribution map with a reef distribution area of 13.18 ha or 47.55% of the total shallow water area. The accuracy test found an accuracy value of 80% with a kappa coefficient 0.7, where the category is good and the level of trust is moderate. The condition of coral reef cover based on live corals in the waters of Setan Island is in the Fair and Poor categories. Percentages range from 0.33% to 31.36%. The dominating lifeform types are coral massive and coral submassive